Introduction to The Utilization of Digital Branding in SME Businesses in Sub-District of Kembangan Selatan - Cicilia, Orlin; Putra, Muhammad Syah Irsan Ratu (EQUATOR SINAR AKADEMIA, 2025)
The business world must be thoroughly explored by businessman, especially in gaining market trust and maintaining it. The trust can be directly obtained through appropriate marketing and branding which is suitable with the characteristics of the business and the products sold. This community service initiative focuses on providing detailed explanations about the utilization of digital branding for SME businesses in the Kembangan Selatan sub-district. The objective of this community service initiative is to introduce the necessity for business owners to implement digital branding, ensuring that the market share they achieve is not limited to offline channels but also extends to online platforms. The outcomes of the community service activity are to ensure that SME owners participating in the activity gain a proper understanding of digital branding to develop appropriate marketing strategies for their product sales.